Incidentally observed 15-meter-long tapeworm during surgery in a patient with newly diagnosed gastric cancer - Koca, Nizameddin; Celik, Oktay; Duzci, Uygar; Gullu Koca, Tuba (The European Research Journal, 2016)
Parasitic infestations are mostly encountered in underdeveloped or developing countries. Taenia saginata is the most frequently found genus in Turkey and cases occur particularly in the Southeastern Anatolian Region. A 57-year-old woman admitted to hospital with the complaints of weakness, weight lose and abdominal pain. Gastroscopy was performed and a tumoral mass was observed. Pathologic evaluation of the endoscopic biopsies was reported as signet ring cell gastric carcinoma. Tapeworm was incidentally observed when the incision was made for jejunal bypass. Fifteen-meter-long parasite was extracted. There are not enough studies and case reports that questioned the relationship between taeniasis and cancer.